PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM INOVASI PENDIDIKAN MTs. AL-AMIRIYYAH BLOKAGUNG BANYUWANGI - Moh. Harun Al Rosid; Hidayatul Hasanah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
The purpose of this research: (1) To seek on how the role of headmaster of MTs. Al-Amiriyyah in academic year 2019/2020, (2) To find educational Innovations of MTs. Al-Amiriyyah in academic year 2019/2020 (3) To find the developers and inhibitors aspect of educational innovation at MTs. Al-Amiriyyah in academic year 2019/2020. This research is using a descriptive qualitative methodology, and using an interview for gathering up the information, observations and documentation. Analyzing data using three models interactives, while the data validation using triangulation. Results of the research: The Role of headmaster of MTs. Al-Amriyyah Blokagung: (1) Planning, (2) Implementation, (3) Evaluation, (4) Communication. While Educational Innovation at MTs. Al-Amiriyyah Blokagung: (1) Capable to seek, to find, and adopting new ideas from other individuals, (2) Capable to renew in teaching and studying process aspect and counseling, recruiting and accompanying new teacher and staff, to re new the human resources in committe and society. After being classified between developers and inhibitors from the result of the researsh, which is formulated in the role of headmaster of educational innovation at MTs. Al-Amiriyyah Blokagung: (1) The role of headmaster the weakness in management changed into opportunities, (2) Cooperation needed in order increase newer innovation, (3) New management needed to make so that facilities and infrastructure and resources being fulfilled.